Pemberdayaan Ekonomi Terhadap Masyarakat Binaan di Lembaga Pemasyarakatan Subang dan Garut Melalui Peningkatan Keterampilanberbasis Entrepreneurship - Imas Rosidawati Wiradirja; Fontian Munzil; Rubi Robana (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2015)
Correctional systems are maintained in order to establish patronages to be fully human, aware of sins, improve themselves, and not to repeat the criminal act so that they can be accepted by society. In KKN-PPM, Universities and Penitentiary in Garut and Subangare cooperating one another in providing working guidance in a variety of competitive skills which has the objective to focus on the process of re-empowerment of inmates as well as sharpening human resources toward the prisoners. The method implemented is participatory methodwithin coaching inmates by giving community-based corrections. KKN-PPM has economic potential that can be enhancedits role through inmates empowerment at Class II A Subang and Class II B Garut correctional facilitiesby involving students from interdisciplinary, they are Agriculture Economic, and Law major. Based on the data, the number of the correctional facility and penitentiary inmates in Indonesia are around 76% including the productive age. The ultimate purpose of the correctional system is reuniting prisoners with the society, as good citizens and being more responsible.The ex-patronages in the community are expected to building the society and not the other wayor becoming an obstacle overthe development.